2015
DOI: 10.1007/s00330-015-3818-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-time eye lens dose monitoring during cerebral angiography procedures

Abstract: Objectives: To develop a real-time dose-monitoring system to measure the patient's eye lens dose during neuro-interventional procedures. Methods: Radiation dose received at left outer canthus (LOC) and left eyelid (LE) were measured using Metal-Oxide-Semiconductor Field-Effect Transistor dosimeters on 35 patients who underwent diagnostic or cerebral embolization procedures. Results: The radiation dose received at the LOC region was significantly higher than the dose received by the LE. The maximum eye lens dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…As defined, direct measurement can be conducted by either placing the dosimeter on the patient's skin surface or inserting it within an anthropomorphic phantom. Various dosimeters have been used in the literature, such as TLD (thermo-luminescent dosimeter), OSLD (optically stimulated luminescent dosimeter), RPLGD (radio-photoluminescent glass dosimeter), MOSFET(Metal-oxide-semiconductor field-effect transistor), MOSkin detector, thin-film detector, and radiochromic film [15][16][17][18][19][20][21].…”
Section: No Computational Modellingmentioning
confidence: 99%
“…As defined, direct measurement can be conducted by either placing the dosimeter on the patient's skin surface or inserting it within an anthropomorphic phantom. Various dosimeters have been used in the literature, such as TLD (thermo-luminescent dosimeter), OSLD (optically stimulated luminescent dosimeter), RPLGD (radio-photoluminescent glass dosimeter), MOSFET(Metal-oxide-semiconductor field-effect transistor), MOSkin detector, thin-film detector, and radiochromic film [15][16][17][18][19][20][21].…”
Section: No Computational Modellingmentioning
confidence: 99%
“…However, the inconvenient truths were that only 4.51% participants wore leaded glasses to protect their eyes, although the eye was one of the most sensitive organs to radiation exposure [ 34 ] . Only 19.17% participants reported wearing real-time dosage monitor, although real-time dosage monitor was well validated strategy to minimize radiation exposure [ 35 ] . Only 30.45% participants reported wearing thyroid gland shield, although radiation-induced thyroid cancer has been well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Kawauchi et al 15) reported that left lens exposure on diagnostic cerebral angiography was significantly higher than right lens exposure. Furthermore, Safari et al 13) placed a MOSFET dosimeter on the eyelid from the lateral side of the left eye for lens dose monitoring. This was because a lateral X-ray tube had been installed on the left side of the patient.…”
Section: Measurement Of the Patient Lens Dosementioning
confidence: 99%
“…Safari et al 13) measured the real-time lens dose using a MOSFET dosimeter for endovascular diagnosis/treatment of the head area. However, concerning the dose measured, the characteristics of the dosimeter were not considered, and the value may have been markedly influenced by the directional dependency of the MOSFET dosimeter.…”
Section: Introductionmentioning
confidence: 99%